Practical data analytics for innovation in medicine : building real predictive and prescriptive models in personalized healthcare and medical research using AI, ML, and related technologies /: building real predictive and prescriptive models in personalized healthcare and medical research using AI, ML, and related technologies. (2022) - Miner, Gary; Miner, Linda A; Burk, Scott; Goldstein, Mitchell; Nisbet, Robert; Walton, Nephi; Hill, Thomas
No abstract available